THE IMPACT OF THE GLOBAL FINANCIAL CRISIS ON THE MARKET EFFICIENCY OF CAPITAL MARKETS OF SOUTH EAST EUROPE - STOITSOVA-STOYKOVA, ANI; Tsenkov, Vladimir (International Journal of Contemporary Economics and Administrative Sciences, 2017)
The study uses the GARCH models to estimate market efficiency of eleven stock markets from South East Europe (SEE) - Bulgaria, , Croatia, Greece, Serbia, Slovenia, Turkey, Romania, Montenegro, Macedonia, Banja Luka and Sarajevo (Bosnia and Herzegovina) over the period from 2005 to 2015 with the accent on the effect of the global financial crisis of 2008 on the market efficiency.  The results reveal that eight of eleventh of analyzed markets can be defined as market inefficient according to the Efficient Market Hypothesis (EMH) during the whole studied period. From pre-crisis to crisis period five of the SEE indices worsen their market efficiency in the terms of the weak form of the EMH. The group of indices with relatively high market efficiency during the post-crisis period is the largest one in comparison with the previous periods. All things considered, it seems reasonable to assume that SEE markets aren’t homogeneous and uniform in the contest of EMH.